Adaptation of Students to Academic mobility: Psychological and Pedagogical Mechanisms and Practices (Journal of Educational Sciences, 2026)
The article addresses the problem of students’ adaptation to academic mobility in the context of the internationalization of higher education. The relevance of the study is determined by the growing scale of international mobility and the need to ensure not only access to educational programs but also effective adaptation of students to a new academic and socio-cultural environment. The aim of the research is to identify and substantiate psychological and pedagogical mechanisms of student adaptation, as well as to develop and test effective support practices within the university environment.The methodological framework is based on a mixed-methods approach combining quantitative and qualitative research methods. The empirical base includes a sample of 128 students from the Caspian University of Technology and Engineering named after Sh. Yessenov and Karaganda University named after Academician E.A. Buketov. The diagnostic tools included the socio-psychological adaptation methodology by C. Rogers and R. Dymond, as well as surveys, interviews, and content analysis.The results of the initial diagnostics revealed that the level of student adaptation is characterized by a relative predominance of the academic component, with insufficient development of socio-cultural and psychological adaptation. In response to the identified gaps, a model of psychological and pedagogical support was developed, including three key components: academic advising, intercultural support, and the development of self-regulation and autonomy skills.The implementation of the model demonstrated its effectiveness: the overall adaptation index increased from 3.58 to 4.12, the proportion of students with a high level of adaptation increased, and the percentage of students with a low level decreased. The most significant improvements were observed in emotional comfort, adaptability, and internal locus of control, indicating the formation of adaptive strategies.The findings confirm that successful student adaptation to academic mobility requires a comprehensive system of psychological and pedagogical support. The practical significance of the study lies in the development of a model and a set of effective practices that can be implemented in university settings to enhance the quality of academic mobility and ensure students’ sustainable integration into the international educational environment.Keywords: academic mobility, adaptation, psychological and pedagogical mechanisms, intercultural competence, internationalization, student support.